Factors that Influence the Reality of Performance Accountability in Government Institutions (Empirical Study in Government Deli Serdang District) - Yuni Syahputri; May Hana Bilqis R; Hasbiana Dalimunthe; Hesti Sabrina; Sari Nuzullina Rahmadhani (Budapest International Research and Critics University, 2019)
This study aims to determine whether the commitment of management, decision making authority, organization culture is partially affected and simultaneously to the accountability performance in government agency to improve government performance. This research method is to use a casual research design. The sample is determined by using the technique of purposive sampling.The population in this research are all employees of the Unit of work Tools (SKPD) Government of Deli Serdang. The sample used in this study is structural officials (Echelon 2, 3 and 4), with a total sample of 60. The data in this study is the primary data obtained from questionnaires distributed directly to the respondent. Data analysis model used was multiple linier regression. Testing the quality of data used is the test validity and reability testing. Classic assumption test was used for normality test, test heterokedastisitas, and tes multikolinearitas. Hypothesis testing using the determinant coefficient, simultaneous test (test-F), partial test (test-t).The results show that management commitment partially has a positive influence on performance accountability. Decision making authority partially has a positive influence on performance accountability. Organization culture partially has a positive influence on performance accountabilitypartially has a negative influence on performance accountability. Simultaneously commitment management, decision making authority, organization culturehave a positive and significant influence on performance accountability.